Peran UMKM dalam menghadapi Society 5.0 - Senen Senen; Syawaludin . Syawaludin; Heri Saputra (Universitas Pamulang, 2022)
Pandemic not only caused a large number of casualties, but also hit the economies of various countries, including Indonesia. Many business sectors have collapsed and even went bankrupt as a result of this pandemic. Micro, Small and Medium Enterprises (UMKM) are not spared from the pandemic as a result of the unpreparedness of the majority of MSME actors in dealing with Covid19. Although various ways have been carried out, including digital transformation, it turns out that the readiness of MSME actors with technology and internet connectivity is still an obstacle. So that a real synergy and collaboration is needed between the government, business actors, and the community in realizing the digital transformation of MSMEs.Keywords: Society, MSME,5.0